Predicting chemotherapy toxicity in multiple myeloma: the prognostic value of pre-treatment serum cytokine levels of interleukin-6, interleukin-8, monocyte chemoattractant protein-1, and vascular endothelial growth factor - Mielnik, Michał; Podgajna-Mielnik, Martyna; Szudy-Szczyrek, Aneta; Homa-Mlak, Iwona; Mlak, Radosław; Gorący, Aneta; Hus, Marek (Frontiers in Immunology, 2024)
Introduction Multiple Myeloma (MM), a prevalent hematological malignancy, poses significant treatment challenges due to varied patient responses and toxicities to chemotherapy. This study investigates the predictive value of pretreatment serum levels of interleukin-6 (IL-6), interleukin-8 (IL-8), monocyte chemoattractant protein-1 (MCP-1), and vascular endothelial growth factor (VEGF) for chemotherapy-induced toxicities in newly diagnosed MM patients. We hypothesized that these cytokines, pivotal in the tumor microenvironment, might correlate with the incidence and severity of treatment-related adverse events. Methods We conducted a prospective observational study with 81 newly diagnosed MM patients, analyzing serum cytokine levels using the multiplex cytometric bead assay (CBA) flow cytometry method. The study used non-parametric and multivariate analysis to compare cytokine levels with treatment-induced toxicities, including lymphopenia, infections, polyneuropathy, and neutropenia. Results Our findings revealed significant associations between cytokine levels and specific toxicities. IL-8 levels were lower in patients with lymphopenia (p=0.0454) and higher in patients with infections (p=0.0009) or polyneuropathy (p=0.0333). VEGF concentrations were notably lower in patients with neutropenia (p=0.0343). IL-8 demonstrated an 81% sensitivity (AUC=0.69; p=0.0015) in identifying infection risk. IL-8 was an independent predictor of lymphopenia (Odds Ratio [OR]=0.26; 95% Confidence Interval [CI]=0.07-0.78; p=0.0167) and infection (OR=4.76; 95% CI=0.07-0.62; p=0.0049). High VEGF levels correlated with a 4-fold increased risk of anemia (OR=4.13; p=0.0414). Conclusions Pre-treatment concentrations of IL-8 and VEGF in serum can predict hematological complications, infections, and polyneuropathy in patients with newly diagnosed MM undergoing chemotherapy. They may serve as simple yet effective biomarkers for detecting infections, lymphopenia, neutropenia, and treatment-related polyneuropathy, aiding in the personalization of chemotherapy regimens and the mitigation of treatment-related risks.